Sociological aspects of medicine and population unbalanced relationships in contemporary Russia - T V Semina (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2015)
The article considers sociological aspects of one of the most complex and urgent problems of the contemporary Russian society - the growing imbalance of social relationships between patients and doctors. Undoubtedly, in medicine each group - doctors and patients - is an element of poorly structured social network and an integral part of all types of interaction in the prevention and treatment of various diseases. This system of relationships is institutionalized and complex in itself, but social and economic processes can complicate or facilitate its functioning. Unfortunately, the growth of social differentiation in the Russian society in the last decades had a negative impact on all spheres of life including healthcare. Under given conditions and social stratification trends each group - doctors and patients - has developed specific value orientations as a kind of professional and personal quintessence of the current fundamental values. In particular, dissatisfaction with the financial situation in the light of work efforts and high level of education explains why doctors consider their social status inadequate and are forced to satisfy their material needs with the help of illegal means. The author proposes some measures to reduce the imbalance of medicine and society relationships in the contemporary Russian society, which suggest changing traditional models of healthcare and conflict management through the purposeful influence on the subject and object of the unbalanced relationships.